The Role of Change Management in Improving Organizational Performance - Mukhlis, Muhammad; Tyas, Ari Anggarani Winadi Prasetyoning (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
An organization's achievement of operational efficiency goals and objectives. The ability of an organization to meet its targets effectively and efficiently is organizational performance. Communication and management technology innovations have revolutionized the way we do almost everything. As the pace of change accelerates, the demand for professionals who can help organizations implement and manage these changes and realize organizational benefits also increases. This research aims to determine the concept of the role of change management in improving organizational performance. This research uses a literature review method with data obtained through searching for books, articles, journals, and previous research results on similar topics. This research concluded that change management plays an important role in facilitating a smooth transition from current conditions to desired future conditions. By using structured methodologies and tools, organizations can analyze the impact of change, identify potential risks and challenges, and develop comprehensive plans to mitigate them. A well-executed change management approach will minimize disruption, reduce downtime, and ensure that employees and stakeholders are adequately prepared for change.